Epithermal Gold-Silver Deposits in Western Java, Indonesia: Gold-Silver Selenide-Telluride Mineralization - Yuningsih, Euis Tintin; Matsueda, Hiroharu; Rosana, Mega Fatimah (Geological Agency, 2014)
DOI: 10.17014/ijog.v1i2.180The gold-silver ores of western Java reflect a major metallogenic event during the Miocene-Pliocene and Pliocene ages. Mineralogically, the deposits can be divided into two types i.e. Se- and Te-type deposits with some different characteristic features. The objective of the present research is to summarize the mineralogical and geochemical characteristics of Se- and Te-type epithermal mineralization in western Java. Ore and alteration mineral assemblage, fluid inclusions, and radiogenic isotope studies were undertaken in some deposits in western Java combined with literature studies from previous authors. Ore mineralogy of some deposits from western Java such as Pongkor, Cibaliung, Cikidang, Cisungsang, Cirotan, Arinem, and Cineam shows slightly different characteristics as those are divided into Se- and Te-types deposits. The ore mineralogy of the westernmost of west Java region such as Pongkor, Cibaliung, Cikidang, Cisungsang, and Cirotan is characterized by the dominance of silver-arsenic-antimony sulfosalt with silver selenides and rarely tellurides over the argentite, while to the eastern part of West Java such as Arinem and Cineam deposits are dominated by silver-gold tellurides. The average formation temperatures measured from fluid inclusions of quartz associated with ore are in the range of 170 â 220Â°C with average salinity of less than 1 wt% NaClequiv for Se-type and 190 â 270Â°C with average salinity of 2 wt% NaClequiv for Te-type.